2021
DOI: 10.1111/geb.13426
|View full text |Cite
|
Sign up to set email alerts
|

Geographical homogenization but little net change in the local richness of Canadian butterflies

Abstract: Aim: Recent studies have found that local-scale plots measured through time exhibit marked variation in the change in species richness. However, the overall effect often reveals no net change. Most studies to date have been agnostic about the identities of the species lost/gained and about the processes that might lead to these changes.Generalist traits might be crucial in allowing species to colonize new plots or remain resilient in situ, whereas environmental filtering might remove specialists. We test wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 275 publications
(145 reference statements)
4
5
0
Order By: Relevance
“…Overall, our results support the hypothesis that small-and largeranged species differ in how they are responding to the last several decades of the Anthropocene. These results generalize previous smaller-scale studies [5][6][7]11,12 to suggest this is a common phenomenon. With our current analyses, however, we cannot directly address the drivers of this result, nor can we specifically determine potential mechanisms behind this overall result for a multitude of taxa, geographic regions, and scales on which the individual studies took place.…”
Section: Caveats and Implicationssupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, our results support the hypothesis that small-and largeranged species differ in how they are responding to the last several decades of the Anthropocene. These results generalize previous smaller-scale studies [5][6][7]11,12 to suggest this is a common phenomenon. With our current analyses, however, we cannot directly address the drivers of this result, nor can we specifically determine potential mechanisms behind this overall result for a multitude of taxa, geographic regions, and scales on which the individual studies took place.…”
Section: Caveats and Implicationssupporting
confidence: 90%
“…2b). This result is consistent with several smaller-scale regional analyses [5][6][7]11,12 , and may reflect the capacity of large-ranged species to tolerate changing environmental conditions as a result of broader environmental tolerances (e.g., generalist strategies), and/or greater dispersal capacities 8,9 .…”
Section: Relationships Between Species Range Size and Occupancy Changesupporting
confidence: 89%
See 1 more Smart Citation
“…However, not all analyses of species richness change find trends centred on zero. For example, species richness increases were found among coastal marine communities [43], temperate marine organisms [44], mountainous plants [45] and Canadian butterflies [46] and invertebrate communities [114]. A review of bird diversity changes found that increases in species richness was the most commonly observed pattern at local scales [47,115].…”
Section: Patterns In Recent Biodiversity Changementioning
confidence: 99%
“…[41]) this does not provide direct evidence of homogenization. Among studies of how betadiversity has changed through time, there are consistent signs of homogenization for marine fishes in Scotland [62], freshwater macroinvertebrates in New Zealand [63], Canadian butterflies [46] and birds [47]. Yet, not all studies show homogenization.…”
Section: (C) Spatial Beta-diversitymentioning
confidence: 99%